Spatiotemporal Analysis of Oklahoma Tobacco Helpline Registrations Using Geoimputation and Joinpoint Analysis. (September 2019) - Dilekli, Naci; Janitz, Amanda; Martinez, Sydney; Gopalani, Sameer; Dougherty, Tyler; Williams, Aaron; Sabzi, Hamed Zamani; Campbell, Janis
Abstract : Objective: Tobacco quitlines provide free smoking cessation telephone services to smokers interested in quitting tobacco. We aimed to explore spatial and temporal analyses of registrations to the Oklahoma Tobacco Helpline including those of any racial group and American Indians (AI) from January 1, 2006, to June 30, 2017. This will allow tribal and community organizations, such as the Oklahoma Tribal Epidemiology Center, to better implement and evaluate public health prevention efforts at a smaller geographic area using the larger geographic units that are publicly available. Design: Retrospective, descriptive study. Setting: Oklahoma. Participants: Registrants to the Oklahoma Tobacco Helpline. Main Outcome Measures: To evaluate the spatial distribution of Helpline participants using geoimputation methods and evaluate the presence of time trends measured through annual percent change (APC). Results: We observed increased density of participants in the major population centers, Oklahoma City and Tulsa. Density of AI registrations was higher in the rural areas of Oklahoma where there is a larger tribal presence compared with participants of any racial group. For all racial groups combined, we identified 3 significant trends increasing from July 2008 to March 2009 (APC: 10.9, 95% confidence interval [CI], 0.8-21.9), decreasing from March 2009 to May 2014 (APC: −0.8, 95% CI: −1.1 to −0.4), and increasing from May 2014 to June 2017 (APC: 0.8, 95% CI: 0.0-1.6). The number of AI registrations to the Helpline increased significantly from July 2008 to March 2009 (APC: 12.0, 95% CI: 2.0-22.9) and decreased from March 2009 to June 2014 (APC: −0.7, 95% CI: −1.0 to −0.3). Conclusions: Results of this project will allow the Helpline to efficiently identify geographic areas to increase registrations and reduce commercial tobacco use among the AI population in Oklahoma through existing programs at the Oklahoma Tribal Epidemiology Center. Abstract : Supplemental Digital Content is Available in the Text.